2015
DOI: 10.1016/j.ejor.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Revenue management under customer choice behaviour with cancellations and overbooking

Abstract: In many application areas such as airlines and hotels a large number of bookings are typically cancelled. Explicitly taking into account cancellations creates an opportunity for increasing revenue. Motivated by this we propose a revenue management model based on Talluri and van Ryzin [27] that takes cancellations into account in addition to customer choice behaviour. Moreover, we consider overbooking limits as these are influenced by cancellations. We model the problem as a Markov decision process and propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Whereas it is complicated to develop tractable solution methods and accurate parameter estimation methods that perform well on computation time, taking a relevant model extension (based on exploratory data analysis) into account can have substantial impact on revenue, as is reported in literature. For example, the seminal model by Talluri and van Ryzin (2004b) increased revenue up to 12% compared to 1-2% differences in other literature at the time, by incorporating customer choice-behaviour; and Sierag et al (2015) showed that by incorporating cancellations into the Talluri and van Ryzin (2004b) model, a substantial (additional) impact on revenue, up till 20%, could be achieved. The following theoretical proposition is, therefore, formulated.…”
Section: Daily Seasonalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas it is complicated to develop tractable solution methods and accurate parameter estimation methods that perform well on computation time, taking a relevant model extension (based on exploratory data analysis) into account can have substantial impact on revenue, as is reported in literature. For example, the seminal model by Talluri and van Ryzin (2004b) increased revenue up to 12% compared to 1-2% differences in other literature at the time, by incorporating customer choice-behaviour; and Sierag et al (2015) showed that by incorporating cancellations into the Talluri and van Ryzin (2004b) model, a substantial (additional) impact on revenue, up till 20%, could be achieved. The following theoretical proposition is, therefore, formulated.…”
Section: Daily Seasonalitymentioning
confidence: 99%
“…As was found in the analysis, on average the closer to the day of arrival, the more clients booked, but this finding did not reveal the nature of the demand distribution. Revenue management literature generally assumes a (nonhomogeneous) Poisson distribution (e.g., McGill and van Ryzin, 1999;Bitran and Caldentey, 2003;Talluri and van Ryzin, 2004b;Sierag et al, 2015). That is, demand per time period is modelled as a homogeneous Poisson process.…”
Section: Probability Distribution Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Koide and Ishii (), Sierag et al. (), and Chua et al. () present models studying hotel room allocations with early‐discount, cancellation, and overbooking facilitated by OTAs.…”
Section: Introductionmentioning
confidence: 99%
“…In a related work, Netessine and Shumsky (2005) considered the equilibrium allocation of seat capacity between fare classes and booking limits when firms compete under the same price points. Recently, Sierag et al (2015) propose a revenue management model that takes into account of cancellations and customer choice behaviour. Using models to calibrate the parameters, they design efficient heuristic solution methods to optimize revenue.…”
Section: Introductionmentioning
confidence: 99%